Radiosurgery is an Effective Treatment for Recurrent Esthesioneuroblastoma: A Multicenter Study - Van Gompel, Jamie J.; Link, Michael J.; Sheehan, Jason P.; Xu, Zhiyuan; Mathieu, David; Kano, Hideyuki; Lunsford, L. Dade (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective Esthesioneuroblastoma (ENB) is a rare malignant neuroendocrine neoplasm that is prone to both local and metastatic recurrence. Local recurrence may often be treated with repeat resection. However, stereotactic radiosurgery (SRS) offers a noninvasive option.Design Prospective database review.Participants Gamma knife prospective databases were queried at all institutions within the North American Gamma Knife Consortium, 16 at the time of this report. All patients who had undergone SRS for ENB were included.Main Outcome Measure Response of recurrent ENB to SRS.Results A total of 31 locally recurrent tumors in 13 patients were treated with SRS. The median age was 49 years (range: 19–79 years). At a median follow-up of 36 months (range: 1–100 months), 13 (48%) treated tumors were smaller, 11 (41%) were stable, and 3 (11%) showed continued growth following SRS. Univariate analysis did not find any significant factor relating to failure of treatment. Notably, no treatment-related complications (0%) were observed in this cohort.Conclusion SRS appears to provide a safe and effective option for treatment of recurrent intracranial ENB. Overall, 89% of treated tumors were controlled in this multi-institutional study.
Keywords: esthesioneuroblastoma; olfactory neuroblastoma; stereotactic radiosurgery; gamma knife